The Use Of The Flipped Classroom Learning Method To Increase Students' Active Participation In Islamic Religious Education Learning At Smp Negeri 1 Sitinjo, Dairi Regency - Pasi, Lady; Abdurrasyid, Abdurrasyid (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to analyze the use of the Flipped Classroom learning method in enhancing students' active participation in Islamic Religious Education (PAI) at SMP Negeri 1 Sitinjo, as well as to identify its supporting and inhibiting factors. The Flipped Classroom method is an instructional approach that reverses the traditional structure, where students independently study materials at home through videos or reading materials, while classroom time is utilized for discussions, QA sessions, and problem-solving activities. This research employs a qualitative method with a descriptive narrative approach. Data collection techniques include observation, interviews, and documentation to understand students' perceptions of this method. The findings indicate that implementing the flipped classroom method can enhance students' active participation, both in class discussions and individual assignments. Supporting and inhibiting factors were also identified to provide a comprehensive understanding of the effectiveness of this method.